Determinants of the crowdfunding campaign success in the Areas of Music and Sports - Trindade, G.; Silva, Tiago; Santos, M-C. (CISTI'2017 - 12th Iberian Conference on Information Systems and Technologies, 2017)
This study aims to contribute to a better understanding about the specificities of different crowdfunding areas in attracting the supporters’ attention. Using data from the largest Portuguese platform, PPL, the study compares the determinants of success of the crowdfunding campaigns in two different areas: Music and Sports. The conceptual model is based on a multiple regression specified in a multiplicative way, which is estimated under the assumption that the project is financed. The results show that the success determinants are different according to the crowdfunding area. In the area of Music, the key factors that contribute positively to the success of financing a project are the number of views per project and the level of requested amount per project. In the area of Sports, the factors that explain the success are the number of images per project, the runtime project and being connected online by Facebook and the factors that explain its failure are the time period to launch a project: failure occurs more often for projects launched by March/April or September/October. These results show the importance of specifying properly the management of a campaign and the network management by crowdfunding area and should give rise to new studies for different industries and in different geographic contexts.